Efektivitas Antipiretik Ekstrak Etanol Daun Tapak Dara (Catharanthus roseus) pada Mencit (Mus musculus) - Haryanto Haryanto; Aqilah Najwa (Inovasi Kesehatan Global, 2025)
Indonesia, considered the country with the second-highest level of biodiversity in the world after Brazil, possesses extraordinary biological wealth that remains underutilized. The field of traditional medicine utilizes natural resources to prevent and treat physical and mental disorders. Periwinkle, or Catharanthus roseus, is one of the most widely used plants due to its abundance of bioactive phytochemicals, such as alkaloids, flavonoids, saponins, and tannins. The ethanol extract from Periwinkle leaves has the potential to act as a natural antipyretic agent that can reduce body temperature during fever. The purpose of this study is to review and analyze previous research findings on the antipyretic effects of ethanol extract from Periwinkle leaves on mice (Mus musculus). According to a literature review from various sources, the ethanol extract of Periwinkle leaves demonstrates a comparable level of effectiveness to synthetic antipyretic drugs in lowering the body temperature of fever-induced mice. Furthermore, the content of active compounds and the antipyretic performance of this plant are influenced by its variety and environmental factors. Body temperature begins to decrease one hour after extract administration and reaches its peak reduction at the third hour. Therefore, Periwinkle may serve as an alternative natural antipyretic remedy. However, further research is necessary to standardize its usage and conduct clinical trials on humans.